PROFESSIONAL PERFORMANCE AND EDUCATIONAL PROGRAM FOR PHYSICAL EDUCATION TEACHERS (Fiep Bulletin - online, 2012)
This paper was produced as a result of a serious concern about the performance and thecontinuous development of physical education teachers in the state of Yucatan, Mexico, where theinvestigative process took place. Many considerations are made in relation to professionalperformance, professionalization, and the importance of pedagogy, among others. According to theobservations, the professional preparation of physical education teachers is mandatory and can beachieved by means of an educational program aiming at improving the knowledge and the abilities ofthese teachers. After many considerations regarding the theoretical, methodological basis andresults of the diagnosis carried out, the paper presents a preliminary proposal for an educationalprogram for physical education instructors.
Keywords: physical education; professional performance; educational program